Ancient metalworking in South America: A 3000-year-old copper mask from the Argentinian Andes - (:unkn) unknown (Cambridge University Press, 2017)
Metallurgy in pre-Columbian America first developed in the Andes, and Peru has long been considered to be the initial point of origin. The recent discovery of an anthropomorphic copper mask in north-west Argentina, however, draws new attention to the southern Andes as a centre of early metalworking. Found in a funerary context c. 3000 BP, at a time of transition from mobile hunter-gatherer bands to agro-pastoral villages, the mask from Bordo Marcial shows that the Cajón Valley and its surrounding region was an important locus for copper metallurgy. To date, the mask is the oldest intentionally shaped copper object discovered in the Andes, and suggests that more than one region was involved in the origin of this technology.

Cortés, L. y Scattolin, M. (2017). Ancient metalworking in South America: A 3000-year-old copper mask from the Argentinian Andes. Antiquity, 91(357), 688-700.
Fil: Cortés, Leticia Inés. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad de Buenos Aires. Instituto de las Culturas; Argentina
Fil: Scattolin, María Cristina. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad de Buenos Aires. Instituto de las Culturas; Argentina
Keywords: 3000 BP; Argentina; Metallurgy; Pre-Hispanic; Southern Andes; Technology